تحليل التماسك المعجمي في سورة القيامة - Hijjah, Shifany Maulida; Nawawi, Mukhshon; El Zahraa, Fatima (Kalimatuna: Journal of Arabic Research, 2023)
This research is motivated by Sayyid Qutub’s assumption in his book (Fii Zilaal Al-Qur’an) that meaningful cohesion study has been carried out in the Al-Qur’an, but has not been studied literally and lexically. There was the impression that the lexical cohesion was the important thing to understand the meaning of Al-Qur’an. Lexical cohesion is a cohesion that associated with meaning and formed by the semantic relationship between another lexicon. In addition to the researcher chose the Surah Al-Qiyamah as the object of research to analyze the lexical cohesion devices that contained in Surah Al-Qiyamah by using Halliday and Ruqaiya’s theory of lexical cohesion. Halliday and Ruqaiya see lexical cohesion as being formed of two aspects: reiteration (repitition, synonym, antonym, hyponym) and collocation. Therefore, this research is trying to answer how many devices of lexical cohesion are contained in Surah Al-Qiyamah.